Analisis Kelayakan Finansial Driver Taxy Online (Studi Kasus Maxim Car Pekanbaru) - Hendra Taufik; Septia Pusvita Sari; Rian Tri Komara Irana (Departemen Teknik Sipil, Fakultas Teknik Universitas Riau, 2022)
Maxim a company engaged online taxy that has invaded Pekanbaru in 2019. The development of Maxim as online transportation service in Pekanbaru is fairly rapid and accommodates lot of workers and is used as the main and side source of income by some drivers. The investment spent in the field of online transportation requires considerable costs, so it is necessary conduct research studies. The purpose of research is to determine the income of drivers, analyze the financial feasibility of online taxy, especially for car vehicles, namely Maxim car. Research sites in 8 strategic locations in Pekanbaru as many as 44 respondents. The method used in data collection is the direct interview method by asking several questions on the questionnaire. The data needed are investment data, operational costs, fixed costs, income, service and maintenance. As a results, the research financial feasibility analysis on Maxim car drivers, it was found that main job average IRR value of 4%. Average value of NPV is: Rp.313,949,947. Average value of BCR 2.13 and the value of BCR obtained is greater than one, then the investment is feasible to carry out. Based on the financial analysis already carried out for the main job of the Maxim driver's business is declared feasible to carry out in the five years from the beginning of the investment issued.